Teplizumab and β-Cell Function in Newly Diagnosed Type 1 Diabetes - Ramos, Eleanor L.; Dayan, Colin M.; Chatenoud, Lucienne; Sumnik, Zdenek; Simmons, Kimber M.; Szypowska, Agnieszka; Gitelman, Stephen E.; Knecht, Laura A.; Niemoeller, Elisabeth; Tian, Wei; Herold, Kevan C. (The New England journal of medicine, 2023)
Teplizumab, a humanized monoclonal antibody to CD3 on T cells, is approved by the Food and Drug Administration to delay the onset of clinical type 1 diabetes (stage 3) in patients 8 years of age or older with preclinical (stage 2) disease. Whether treatment with intravenous teplizumab in patients with newly diagnosed type 1 diabetes can prevent disease progression is unknown. In this phase 3, randomized, placebo-controlled trial, we assessed β-cell preservation, clinical end points, and safety in children and adolescents who were assigned to receive teplizumab or placebo for two 12-day courses. The primary end point was the change from baseline in β-cell function, as measured by stimulated C-peptide levels at week 78. The key secondary end points were the insulin doses that were required to meet glycemic goals, glycated hemoglobin levels, time in the target glucose range, and clinically important hypoglycemic events. Patients treated with teplizumab (217 patients) had significantly higher stimulated C-peptide levels than patients receiving placebo (111 patients) at week 78 (least-squares mean difference, 0.13 pmol per milliliter; 95% confidence interval [CI], 0.09 to 0.17; P<0.001), and 94.9% (95% CI, 89.5 to 97.6) of patients treated with teplizumab maintained a clinically meaningful peak C-peptide level of 0.2 pmol per milliliter or greater, as compared with 79.2% (95% CI, 67.7 to 87.4) of those receiving placebo. The groups did not differ significantly with regard to the key secondary end points. Adverse events occurred primarily in association with administration of teplizumab or placebo and included headache, gastrointestinal symptoms, rash, lymphopenia, and mild cytokine release syndrome. Two 12-day courses of teplizumab in children and adolescents with newly diagnosed type 1 diabetes showed benefit with respect to the primary end point of preservation of β-cell function, but no significant differences between the groups were observed with respect to the secondary end points. (Funded by Provention Bio and Sanofi; PROTECT ClinicalTrials.gov number, NCT03875729.).